A new conceptualization of the nurse–patient relationship construct as caring interaction. (22nd October 2020) - Allande Cussó, Regina; Siles González, José; Ayuso Murillo, Diego; Gómez Salgado, Juan
Abstract: The journey through the history of nursing, and its philosophical and political influences of the moment, contextualizes the interest that arose about the nurse–patient relationship after World War II. The concept has always been defined as a relationship but, from a phenomenological approach based on a historical, philosophical, psychological and sociological cosmology, it is possible to re‐conceptualize it as 'caring interaction'. Under the vision of aesthetics and sociopoetics, the object of nursing care is the most delicate, vulnerable and unrepeatable raw material: the person, whose feelings and reciprocity, which must be considered. In addition, it involves the adoption of the socio‐critical paradigm, as it considers the importance of actively involving the person, not just patient anymore, or their family in the nursing cares, optimizing the reciprocity inherent to this interactivity. In short, our philosophical and epistemological approach to the concept of nurse–patient relationship proposes a new conceptualization of it as a caring interaction.